CHINA’S SOFT POWER: THE MAKING OF FOOTBALL SUPERPOWER (‘SOFT POWER’ CINA : MENUJU KEKUATAN ADIDAYA DALAM SEPAKBOLA) - Santosa, Ganjar Ariel (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – A significant economic rise provides an opportunity for China to expand its influence globally, especially in sectors where China does not have strong influences. One of them is football. The average achievement of its National football has pushed the government to implement soft power strategy to improve the quality and the competitiveness of its national football. This strategy is carried out with a strong synergy between the government and private sector businesses nationwide. This paper will analyze how China’s soft power strategy implemented in order to advance its national football and their national pride globally. Keywords : China, soft power, economy, football, investment Abstrak – Kebangkitan ekonomi Cina memberikan peluang untuk memperluas pengaruh secara global, terutama pada sektor-sektor dimana Tiongkok tidak memiliki pengaruh yang cukup kuat. Salah satunya adalah sepakbola. Prestasi sepakbola nasional yang biasa-biasa saja membuat pemerintah menerapkan strategi soft power untuk mendorong perbaikan kualitas dan persaingan sepakbola nasional. Strategi ini dilakukan dengan sinergi yang kuat antara pemerintah dengan sektor bisnis swasta nasional. Makalah ini akan menganalisis bagaimana strategi soft power tersebut diimplementasikan demi kemajuan sepakbola nasional dan kehormatan bangsa di mata dunia. Kata kunci : Cina, soft power, ekonomi, sepakbola, investasi